Kesesuaian Pilihan Jurusan dengan Minat Karir Siswa (Studi Deskriptif pada Siswa SMA/MA di Kota Payakumbuh) - Alfia, Vivi; Afdal, Afdal (Jurnal Aplikasi IPTEK Indonesia, 2023)
This research was motivated by the phenomenon that some students have career interests are not in line with the major in which they live. The purpose of this study was to describe how the match between the choice of majors with career interests of students with descriptive method. The number of samples is 86 students of SMAN 1 Payakumbuh and 77 students of MAN 2 Payakumbuh. The sampling technique using Stratified Random Sampling techniques. The instrument of this research using questionnaires about career interests by using of Holland's theory. Data will be analyzed by classifying the type of personality that tends to lead to the kind personality for science majors and that tends to lead to the social science majors. The next one match majors choice with career interest seen by his personality type. The results of this study are 46.62% of the students have not had a match between the choice of majors with career interests while as many as 53.37% of the students already have a match between the choice of majors with career interests.